2015
DOI: 10.12816/0024918
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Framework of Islamic Governance for Awqaf

Abstract: Along with the revival of waqf (plural awqal) institution, the attention to the call for good governance and best practices of waqf has emerged. It is widely agreed that the best practice of good governance should be adopted as it is one of the critical success factors for revitalizing awqaf institutions. As far as waqf study is concerned, there is no existing study on waqf governance. This is probably because the conception of governance was used exclusively in the commercial sectors. In fact, governance in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…The second theme of waqf accountability-related studies discusses how good governance can improve waqf accountability. Although theoretical in nature, a study by Ihsan and Ayedh (2015) provides a basis to explain the relationship between governance structure and accountability. Meanwhile, another study by Ihsan et al (2016) tried to portray the historical dimension of waqf accountability through examining the existing waqf literatures.…”
Section: Accountability-related Studiesmentioning
confidence: 99%
“…The second theme of waqf accountability-related studies discusses how good governance can improve waqf accountability. Although theoretical in nature, a study by Ihsan and Ayedh (2015) provides a basis to explain the relationship between governance structure and accountability. Meanwhile, another study by Ihsan et al (2016) tried to portray the historical dimension of waqf accountability through examining the existing waqf literatures.…”
Section: Accountability-related Studiesmentioning
confidence: 99%
“…Since the main purpose of waqf is to fulfill non-profit purposes and its nature is similar to non-profit organizations (Ramli & Muhamed, 2013), the definition and measurement of performance for the non-profit organizations will be applied to measure the performance of waqf institutions. In a related view, Ihsan and Ayedh (2015) suggested that waqf institutions have similar characteristics with non-profit organizations and can be considered in the same category, as the formation of these organizations is to benefit the society. Berman (2015, p. 5 performance as "the effective and efficient use of resources to achieve results and objectives".…”
Section: Performance Measurement Of Waqf Institutionsmentioning
confidence: 99%
“…They are also responsible to distribute the zakat fund for beneficaries (Abd. Wahab, et.al, 2017) and also reported the financial statement to the stakeholders as one of the indicator of good governance i.e accountability to Allah and beneficaries (Saad, et.al, 2014;Ihsan and Ayedh, 2015) While according to Ayyagari et.al (2007) there is no similar term, definition or measurement of Small and Medium Enterprises (SMEs) due to the variance term, definition or measurement across the globe. However, the SMEs across the globe share similar characteristics that must included in the SMEs.…”
Section: Repositioning Role Of Zakat Institution (As Smes)mentioning
confidence: 99%
“…The basic principles of good governance which taken from Islamic Values are amanah, adalah and syuro.The application of those values then requires the institution to perform sharia audit, financial audit and etc. (Ihsan and Ayedh; This is important and consider as one of the consequences of Tauhid,i.e the accountability to Allah and mankind (including beneficaries and stakeholders) (Saad, et.al, 2014;Ihsan and Ayedh; In order to maintain the accountability and efficiency of zakat institution, other study discusses about the accountability and efficiency practices of charitable organization. For instance (Abd Wahab and Abdul Rahman;2011) disscussed about the efficiency of Zakat institution using United Nation Development Program (UNDP) good governance standard.…”
Section: A Introductionmentioning
confidence: 99%